Influence Self-Regulated Learning and Self-Efficacy to Academic Performance Economic Olympiad Participants ECOLY 2025 - Aisya Jihan Fernanda; Jun Surjanti (INFLUENCE: INTERNATIONAL JOURNAL OF SCIENCE REVIEW, 2026)
This study examines the influence of Self-Regulated Learning and Self-Efficacy on the Academic Performance of participants in the ECOLY 2025 Economics Olympiad. Preliminary observations indicated that several participants experienced difficulties in managing learning strategies, time allocation, and confidence when facing competition tasks. A quantitative approach was employed using an online questionnaire distributed to 44 ECOLY 2025 participants. The collected data were analyzed through multiple linear regression. The findings revealed that Self-Regulated Learning had no significant effect on Academic Performance (t = 0.909; Sig. = 0.369), while Self-Efficacy also showed no significant effect (t = 0.158; Sig. = 0.875). Simultaneously, both variables did not significantly influence Academic Performance (F = 1.261; Sig. = 0.294), with an Adjusted R Square value of 0.012. These results indicate that Self-Regulated Learning and Self-Efficacy explain only 1.2% of the variation in Academic Performance, whereas the remaining 98.8% is influenced by other factors. The findings suggest that improving students' performance in academic competitions requires greater attention to subject mastery, competition experience, analytical thinking skills, training intensity, and learning environment support.